2008
DOI: 10.1002/hed.20755
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of postsurgical stimulated thyroglobulin levels after initial radioactive iodine therapy in well‐differentiated thyroid carcinoma

Abstract: Stimulated thyroglobulin measurements prior to initial radioactive iodine treatment independently predict future stimulated thyroglobulin positivity in well-differentiated thyroid carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 26 publications
(29 reference statements)
2
21
0
2
Order By: Relevance
“…Exclusion criteria used by included studies are summarized in Table 2. Three studies excluded patients with microcarcinomas (6,16,17), and two studies included only patients with T1 (8) or T1ϩT2 tumors (16). Two studies excluded patients with T4 lesions (13,16), two excluded patients with local lymph node metastases (16,19), and four studies excluded patients with distant metastases at baseline (10,13,16,19).…”
Section: Discussionmentioning
confidence: 98%
“…Exclusion criteria used by included studies are summarized in Table 2. Three studies excluded patients with microcarcinomas (6,16,17), and two studies included only patients with T1 (8) or T1ϩT2 tumors (16). Two studies excluded patients with T4 lesions (13,16), two excluded patients with local lymph node metastases (16,19), and four studies excluded patients with distant metastases at baseline (10,13,16,19).…”
Section: Discussionmentioning
confidence: 98%
“…This is justified by the fact that stimulated thyroglobulin measurements have been shown to be highly sensitive and specific in detecting disease among patients who have undergone total or near-total thyroidectomy and radioactive remnant ablation. 25,[38][39][40] Though early stimulated thyroglobulin measurements may become undetectable with longer follow-up in the absence of therapy, 41,42 we believe that a steady-state titer was attained considering 85% of patients had a stimulated test greater than 1 year after surgery and that the mean time to the stimulated test was 5.8 years after radioactive remnant ablation.…”
Section: Discussionmentioning
confidence: 98%
“…Some investigators reported that preablative Tg levels could be a predictor for progressive or metastatic disease in the long term follow-up period and could be regarded as another criterion together with lymph node invasion for choosing high risk patients [7][8][9][10]. Despite this, preablative Tg level is not as frequently used as postablative Tg level in the clinical practice.…”
Section: Introductionmentioning
confidence: 99%